3D Printing of Bioinspired Biomaterials for Tissue Regeneration. Issue 23 (27th April 2020) - Li, Tian; Chang, Jiang; Zhu, Yufang; Wu, Chengtie
Abstract: Biological systems, which possess remarkable functions and excellent properties, are gradually becoming a source of inspiration for the fabrication of advanced tissue regeneration biomaterials due to their hierarchical structures and novel compositions. It would be meaningful to learn and transfer the characteristics of creatures to biomaterials design. However, traditional strategies cannot satisfy the design requirements of the complicated bioinspired materials for tissue regeneration. 3D printing, as a rapidly developing new technology that can accurately achieve multimaterial and multiscale fabrication, is capable of optimizing the fabrication of bioinspired materials with complex composition and structure. This review summarizes the recent developments in 3D‐printed bioinspired biomaterials for multiple tissue regeneration, and especially highlights the progresses on i) traditional bioinspired designs for biomaterials fabrication, ii) biological composition inspired designs for the 3D‐printed biomaterials, and iii) biological structure inspired designs for the 3D‐printed biomaterials. Finally, the challenges and prospects for the development of 3D‐printed bioinspired biomaterials are discussed. Abstract : 3D printing of bioinspired biomaterials is introduced into the multiple tissue regeneration. By learning the advanced functions and brilliant properties of biologic systems, 3D‐printed biomaterials design from biological composition and structure inspiration are illustrated in this review. Furthermore, the future development and challenges of 3D‐printed bioinspired biomaterials are also discussed.